Overcoming the Weak Generation in Education from the Al-Qur'an Perspective - Nasir, Muhammad; Nawawi, Abd Muid; Zuhri, Saifuddin (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Overcoming the weak generation in education is an urgent need to create an inclusive, sustainable, and competitive society. This research was carried out using the maudhȗ'i method which aims to formulate a response solution based on the perspective of the Al-Qur'an. Research data comes from primary and secondary data collected through library research. Data was analyzed qualitatively and descriptively. The results of this research show that overcoming weak generations according to the perspective of the Qur'an is by protecting from the time of choosing a life partner and providing appropriate parenting from an early age.Overcoming the weak generation in education is an urgent need to create an inclusive, sustainable, and competitive society. This research was carried out using the maudhȗ'i method which aims to formulate a response solution based on the perspective of the Al-Qur'an. Research data comes from primary and secondary data collected through library research. Data was analyzed qualitatively and descriptively. The results of this research show that overcoming weak generations according to the perspective of the Qur'an is by protecting from the time of choosing a life partner and providing appropriate parenting from an early age.